Factors influencing vitamin A supplementation among children aged 6-59 months at a lower-level urban health facility in Nairobi County, Kenya - Odhiambo, Felix Blair; Wanjiru, Kahiga Rose; Okenyoru, Douglas Sendora (International Journal Of Community Medicine And Public Health, 2025)
Background: Vitamin A is vital for child growth, immunity and vision. Despite global initiatives, deficiency persists, affecting 190 million children worldwide, especially in Sub-Saharan Africa (48%). In Kenya, 9.2% of children remain deficient, with only 28% supplementation coverage. In Nairobi, socioeconomic barriers and low awareness hinder uptake, necessitating targeted interventions. Methods: The study adopted a descriptive cross-sectional design conducted between June and December 2024 at Riruta Health Centre, Nairobi County. Participants were mothers of children aged 6–59 months who had resided in the area for at least three months and consented to participate. Using Yamane’s (1967) formula, a sample of 218 was selected through consecutive sampling. Data were collected using structured questionnaires and analyzed using SPSS version 26.0. Results: Results showed that 66% of children aged 6–59 months received Vitamin A supplements. Uptake was significantly associated with child’s age (p=0.001), gender (p=0.015) and mother’s marital status (p=0.001). Economic factors; employment status (p=0.001) and access to health services (p=0.001) and high maternal knowledge of VAD (p=0.001) and VAS (p=0.001) also significantly influenced supplementation Conclusions: The study found 66% Vitamin A Supplementation (VAS) coverage among children aged 6–59 months. Uptake was significantly influenced by child’s age, gender, mother’s marital status, employment status, access to health services and maternal knowledge. To enhance VAS uptake, the study recommends to implement targeted health education, support low-income families and strengthen healthcare infrastructure for effective VAS delivery.